A study in the admissibility of digital evidence in the Malaysian courts / Md. Shazli Munip Abdul Malek…[et al.] - Abdul Malek, Md. Shazli Munip; Bahrim, Noraisyah; Abu Bakar, Muhd. Akmal (Faculty of Law, 2007)
This research was done to fulfil one of the requirements of the Bachelor of Legal Studies program. The research examines the issue of admissibility of digital evidence in Malaysian courts. The issue of authenticity of evidence is not new; however the nature of digital evidence makes it easier for it to be manipulated, altered and tempered. Thus, it is important to determine whether the current laws in Malaysia are sufficient to safeguard evidence in digital forms from being tempered. Two critical issues were discussed in this research. The first issue was whether digital evidence can be considered as evidence in Malaysian courts. The second issue was whether digital forms of evidence are admissible as documentary evidence. To shed some light on the issues concerned, the research had focused on the definition of evidence under the Malaysian Evidence Act and the rules governing the admissibility of documentary evidence. To understand the issue of admissibility of documentary evidence reference were made to Malaysian authors. The research has also examines the position taken by other common law countries such as the United States, Australia, United Kingdom and India on the issue. After examining the problems surrounding admissibility of digital evidence, some recommendations were suggested at the end of this research.